Brief Coping Strategy Enhancement for Distressing Voices: an Evaluation in Routine Clinical Practice. Issue 2 (27th June 2017) - Hayward, Mark; Edgecumbe, Rebecca; Jones, Anna-Marie; Berry, Clio; Strauss, Clara
Abstract : Background: Hearing voices can be a common and distressing experience. Psychological treatment in the form of cognitive behavioural therapy for psychosis (CBTp) is effective, but is rarely available to patients. The barriers to increasing access include a lack of time for clinicians to deliver therapy. Emerging evidence suggests that CBTp delivered in brief forms can be effective and offer one solution to increasing access.Aims: We adapted an existing form of CBTp, coping strategy enhancement (CSE), to focus specifically on distressing voices in a brief format. This intervention was evaluated within an uncontrolled study conducted in routine clinical practice.Method: This was a service evaluation comparing pre–post outcomes in patients who had completed CSE over four sessions within a specialist out-patient service within NHS Mental Health Services. The primary outcome was the distress scale of the Psychotic Symptoms Rating Scale – Auditory Hallucinations (PSYRATS-AH).Results: Data were available from 101 patients who had completed therapy. A reduction approaching clinical importance was found on the PSYRATS distress scale post-therapy when compared with the baseline.Conclusions: The findings from this study suggest that CSE, as a focused and brief form of CBTp, can be effective in the treatment of distressing voices within routine clinical practice. Within the context of the limitations of this study, brief CSE may best be viewed as the beginning of a therapeutic conversation and a low-intensity intervention in a stepped approach to the treatment of distressing voices.